2019
DOI: 10.1182/blood-2019-126232
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns of Inappropriate Plasma Transfusion Practices Using a Novel Multicenter Electronic Data Audit: Over 80 Percent of Plasma Transfused Is Inappropriate

Abstract: Importance: Plasma is frequently transfused to patients who are bleeding or require an invasive procedure and have a deficiency of coagulation factors. Despite published guidelines delineating optimal plasma use, two recent audits have suggested that over 50% of the plasma transfused is unnecessary. Inappropriate utilization of plasma has numerous adverse consequences for the recipient, as well as the health care system. Objective: To determine the proportion of inappropriate plasma use with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…7,27 There are many harms associated with inappropriate coagulation testing, including increased risk of exposure to blood components and products, a cascade of additional investigations and referrals, delays to patient care, patient and physician anxiety, iatrogenic anemia, and additional, often unnecessary costs to the health care system. [3][4][5]7,[9][10][11] In a previous study conducted at our center in the emergency department, the reduction of routine use of PT/aPTT testing in unselected patients was associated with an estimated cost saving of US$56,000 per year. 28 As medical trainees order a significant proportion of laboratory tests at academic centers, this is an important group to target in clinical quality improvement interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,27 There are many harms associated with inappropriate coagulation testing, including increased risk of exposure to blood components and products, a cascade of additional investigations and referrals, delays to patient care, patient and physician anxiety, iatrogenic anemia, and additional, often unnecessary costs to the health care system. [3][4][5]7,[9][10][11] In a previous study conducted at our center in the emergency department, the reduction of routine use of PT/aPTT testing in unselected patients was associated with an estimated cost saving of US$56,000 per year. 28 As medical trainees order a significant proportion of laboratory tests at academic centers, this is an important group to target in clinical quality improvement interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A single‐center Canadian audit of FP use identified 62.6% of FP transfusions were administered for an INR of 0.9 to 1.8 13 . A more recent Canadian audit of FP transfusions at three large tertiary care centers identified that 81.5% of FP was transfused inappropriately, with 21.5% of these transfusions administered to patients with an INR of 1.5 to 1.7 11 . The inappropriate transfusion of FP results in many negative outcomes, including the harm of transfusion reactions and increased costs to the health care system 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, an abnormal PT/INR or APTT may lead the patient down a path of unnecessary investigations, referrals, procedure delays, anxiety, and even inappropriate plasma transfusion, causing potential harm to patient and contributing toward an increased financial burden on the health care system. 1,[6][7][8] The clinical history is an important screening tool for bleeding disorders. 9 To that end, bleeding assessment tools (BATs) such as APTT tests per 100 patients per week), leading to an estimated $6000 in savings per month.…”
Section: Introductionmentioning
confidence: 99%
“…When assessing a patient with a bleeding history, a physician may be falsely reassured by a normal PT/INR and/or APTT. Conversely, an abnormal PT/INR or APTT may lead the patient down a path of unnecessary investigations, referrals, procedure delays, anxiety, and even inappropriate plasma transfusion, causing potential harm to patient and contributing toward an increased financial burden on the health care system 1,6–8 …”
Section: Introductionmentioning
confidence: 99%